2020
DOI: 10.1017/s1478951520001042
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the efficacy of music in palliative care: A scoping review

Abstract: Objective There is an increasing recognition of the significance of music as a complementary therapy in palliative care. Limited studies exist on how music is used as a coping mechanism by palliative care patients. Therefore, the purpose of this scoping review was to explore the efficacy of music interventions for palliative care. Method We conducted a literature search between June and November 2019 in the Cumulative Index of Nursing and Allied Health Literature (CINAHL), British Nursin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 31 publications
0
4
0
2
Order By: Relevance
“…Visando, desta forma, a adoção de cuidados integrais ao longo do percurso da doença, contemplando todas as esferas do indivíduo (corpo físico, mente e espírito), independentemente da faixa etária ou do tratamento direcionado à patologia, trazendo a finitude como um processo natural [13][14][15][16][17] .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Visando, desta forma, a adoção de cuidados integrais ao longo do percurso da doença, contemplando todas as esferas do indivíduo (corpo físico, mente e espírito), independentemente da faixa etária ou do tratamento direcionado à patologia, trazendo a finitude como um processo natural [13][14][15][16][17] .…”
Section: Discussionunclassified
“…Oferecer uma rede de apoio de amparo psicológico por meio da identificação precoce dos sintomas e fatores precursores da ansiedade, estresse, insônia e depressão, também é extremamente importante, além de englobar a humanização e a empatia durante todo cuidado [15][16]18 .…”
Section: Discussionunclassified
“…Dr. William Breitbart Editor-in-Chief Palliative and Supportive Care Dear Editor, I have read with interest the article entitled "Exploring the efficacy of music in palliative care: A scoping review" by Nyashanu et al (2020). With respect to the authors, I do not believe music therapy can be deemed efficacious based on the results as they state.…”
Section: July 12 2021mentioning
confidence: 99%
“…For example, scoping reviews typically don't include quality assessment of publications, as it was the case in Nyashanu et al (2020), but this assessment is essential when formulating recommendations to guide clinical practice (Pham et al, 2014). Even though many studies identified in the scoping review were randomized controlled trials, the lack of quality assessment prevents from making conclusions on efficacy of music therapy in palliative care because the presence of biases that underestimate or overestimate the intervention outcomes was not taken into account (Higgins et al, 2019).…”
Section: July 12 2021mentioning
confidence: 99%
See 1 more Smart Citation